Flagellin from Salmonella enteritidis Enhances the Immune Response of Fused F18 from Enterotoxigenic Escherichia coli - An-Phuc Tran-Mai; Hong-Diep Thi Tran; Quoc-Gia Mai; Kien-Quang Huynh; Thuoc Linh Tran; Hieu Tran-Van (Tropical Life Sciences Research, 2022)
F18 plays an important role in helping Enterotoxigenic Escherichia coli (ETEC) binds to specific receptors on small intestinal enterocytes, followed by secreting of toxins causing diarrhea in post-weaning piglets (post-weaning diarrhea, PWD). However, the F18 subunit vaccine is not sufficient to stimulate an immune response that can protect weaning pigs from F18-positive ETEC (F18+ETEC). Recently, a body of evidence shows that flagellin protein (FliC) helps to increase the immunity of fused proteins. Therefore, in this study, we combined FliC with F18 to enhance the immune response of F18. The f18 gene was obtained from F18+ETEC, then was fused with the fliC gene. The expression of recombinant FliC-F18 protein was induced by Isopropyl-beta-D-Thiogalactopyranoside (IPTG). The purified protein was tested in vivo in mouse models to evaluate the immunostimulation. Results showed that the fusion of FliC and F18 protein increased the production of anti-F18 antibodies. Besides, the anti-F18 antibody in the collected antiserum specifically identified F18+ETEC. This result provides proof-of-concept for the development of subunit vaccine to prevent PWD using F18 antigen.